2002
DOI: 10.1523/jneurosci.22-03-00832.2002
|View full text |Cite
|
Sign up to set email alerts
|

PersistentengrailedExpression Is Required to Determine Sensory Axon Trajectory, Branching, and Target Choice

Abstract: The transcription factor Engrailed (En) directs, in the cockroach cercal system, the shape of the axonal arborization and the choice of postsynaptic partners of an identified sensory neuron (6m). Knock-out of En using double-stranded RNA interference transforms 6m so that it resembles a neighboring neuron that normally does not express the en gene, has a different arbor anatomy, and makes different connections. We characterized the development of 6m and perturbed en expression at different stages. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…When we did use a driver (ato-GAL4 ) that is actually expressed in the precursors but not the early neurons, we found no effect of En knockdown. This apparent postmitotic effect is reminiscent of our previous studies on the cockroach cercal system, which also indicate that En is required postmitotically in sensory neurons to determine first their branching pattern and then their pattern of synaptic connections (Marie et al, 2002). In that system, it seems that, once formed, synapses cannot be altered by En knockdown.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…When we did use a driver (ato-GAL4 ) that is actually expressed in the precursors but not the early neurons, we found no effect of En knockdown. This apparent postmitotic effect is reminiscent of our previous studies on the cockroach cercal system, which also indicate that En is required postmitotically in sensory neurons to determine first their branching pattern and then their pattern of synaptic connections (Marie et al, 2002). In that system, it seems that, once formed, synapses cannot be altered by En knockdown.…”
Section: Discussionsupporting
confidence: 60%
“…En regulates the development of some spinal cord interneurons (Wenner et al, 2000;Simon et al, 2001) and affects the survival of dopaminergic midbrain neurons (Simon et al, 2001;Sgadò et al, 2006). In Drosophila and grasshopper CNS, En controls neuron/ glia fate decisions, neuronal identity, and axon pathfinding (Condron et al, 1994;Lundell et al, 1996;Joly et al, 2007), whereas in cockroach mechanosensory neurons we showed that it also controls axon guidance, synaptic target recognition, and, as a result, escape behavior (Marie et al, 2000(Marie et al, , 2002Marie and Blagburn, 2003;Blagburn and Bacon, 2004;Booth et al, 2009).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this respect it is interesting to note that En1 activity regulates ephrin gene expression in the chick tectum, thereby altering the topographic targeting of retinal axons (Friedman and O'Leary, 1996;Logan et al, 1996). Furthermore, in Drosophila, the expression of synaptic recognition molecules is modulated by engrailed, the fly homolog of En1 (Marie et al, 2002). Interestingly, the recurrent synapses that do form on motor neurons in the En1 mutant mice appear to be functional, because the calbindin ϩ terminals are presynaptic to gephyrin-containing clusters, which are known to be formed and stabilized by activitydependent mechanisms (Kirsch and Betz, 1998;Levi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of En in axonal outgrowth has been demonstrated in mammals and insects (Marie et al, 2002;Saueressig et al, 1999). To address this possibility, we placed dissociated E12 ventral midbrain into a three-dimensional collagen matrix with or without an explant of basal telencephalon of the same age.…”
Section: Engrailed and Axonal Outgrowthmentioning
confidence: 99%